APLIKASI BAHAN BANGUNAN “BAMBU” PADA TEMPAT SANTAI (GAZEBO DAN DEGO-DEGO) MAHASISWA PROGRAM VOKASI UNG - Syafriani; Abdi Gunawan Djafar; Alif Nurrahman l. Masi; Al Dimas F. Darkay (Universitas Bina Taruna Gorontalo, 2023)
This study aims to examine the application of bamboo building materials in the construction of gazebos and relaxation areas (dego-dego) as an implementation of project-based learning for students in the UNG Vocational Program. The research method uses a project-based learning (PBL) approach with stages of preparation, data collection through comparative studies, material delivery by lecturers, and evaluation of bamboo construction products. Activities included field visits to brick and concrete block factories, the creation of concrete models with various mixtures, and the practical application of gazebo construction using bamboo, wood, thatched roofs, palm fiber ropes, and other supporting materials. The results of the study showed a 70% success rate in students' mastery of knowledge and practical skills in applying bamboo as a sustainable construction material. Bamboo has been proven to have optimal structural characteristics as a lightweight, hollow material with bracing properties that strengthen construction. Despite group coordination challenges, this research has made an important contribution to developing an understanding of environmentally friendly construction material diversification and has laid the foundation for the development of sustainable material innovations in the future.